The construction of local convex hull on the task of pattern recognition - Mirzoyan, Kamilov; Mirzaakbar, Hudayberdiev; Alisher, Khamroev (Procedia computer science, 2021)
In this research paper analyzes and explores the problems of pattern recognition methods and biological object identification algorithms. We encountered two different problems in the process. The first is the modernization of the pattern recognition algorithm; the second is associated with the identification of a biological object. The algorithm problem was solved by constructing local convex hull during modernization. In the second, the Orthoptera insect group was selected as a biological object on the recommendation of experts. Orthoptera is a taxonomic insect division that includes locusts and other winged insects. Approaches to determining the characteristics of orthoptera types and preparing their samples, as well as the formation of identification models, are recommended. The algorithm for calculating estimates (ACE) was chosen when identifying the choice of orthoptera. The ACE based on the principle of partial precedence. Approaches to the formation of a training-test selection for the choice of orthopters are proposed. As mentioned above, in this work is proposed to develop an information recognition system designed to solve the problems associated with the identification of Orthoptera Insecta, as well as for the experimental study of the specie of the locust family.